Райковецька культура в Середньому Подніпров’ї - Дяченко, Д.Г. (Археологія і давня історія України, 2021)
Стаття присвячена райковецькій культурі в Середньому Подніпров’ї. Враховуючи досягнення вітчизняної археології у розвитку питання, визначено основні проблеми та можливі шляхи їх вирішення. Розглянуто ґенезис, хронологію й особливості розвитку матеріальної культури райковецьких пам’яток VIII—IX ст. правобережної частини долини Дніпра. The paper is devoted to the Raiky culture in the Middle Dnieper. It reveals major issues of the phenomenon of Raiky culture and their possible solutions considering the achievements of Ukrainian archeologists in this field. The genesis, chronology and features of the development of material culture of the Raiky sites in the 8th—9th centuries of the right-bank of the Dnieper are analyzed. In general the existence of the Raiky culture in the Middle Dnieper region can be described as follows. It was formed in first half of the 8th century in the Tiasmyn basin. The first wheel-made pottery has begun to manufacture quite early, from the mid-8th century (probably at the beginning of the third quarter). At the first stage, the early vessels have imitated the hand-made Raiky forms as well as the Saltovo- Mayaki imported vessels. Significant development of the material culture occurs during the second half of the 8th century. At the same time, the movement of the people of Raiky culture and the population of the sites of Sаkhnivka type has begun in the northern direction which was marked by the appearance of the Kaniv settlement, Monastyrok, and possibly Buchak. This stage is characterized by the syncretism both in the ceramic complex and in the features of design of the heating structures. Numerous influences of the people of Volyntsevo culture (and through them – of Saltovo-Mayaki one) are recorded in the Raiky culture. It is observed not only in direct imports but also in the efforts of the Raiky population to imitate the pottery of Volyntsevo and Saltovo-Mayaki cultures, however, based on their own technological capabilities. The nature of the relationship between the bearers of these cultures is still interesting. The population of Raiky accepts the imported items of Saltovo-Mayaki and Volyntsevo cultures, tries to imitate high-quality pottery of them, and even one can see the peaceful coexistence of two cultures in one settlement — Monastyrok, Buchak, Stovpyagy. However, the reverse pulses are absent. There are no tendencies to assimilate each other. Although, given the number and size of the sites, the numerical advantage of the Volyntsevo population in the region seems obvious. There is currently no answer to this question. The first third of the 9th century became the watershed. The destruction of the Bytytsia hill-fort and the charred ruins to which most of the settlements of the Volyntsevo culture has turned, is explained in the literature by the early penetration of Scandinavians into the region or as result of the resettlement of Magyars to the Northern Pontic region. In any case, this led to a change in the ethnic and cultural situation in the Dnieper basin. According to some researchers, the surviving part of the population of Volyntsevo culture migrated to the Oka and Don interfluve. For some time, but not for long, the settlements of Raiky culture remained abandoned. Apparently, after the stabilization of situation, the residents have returned which is reflected by the reconstruction of the Kaniv settlement and Monastyrok; in addition, on the latter the fortifications have been erected. The final stage of the existence of culture is characterized by contacts with the area of the left bank of Dnieper, the influx of the items of the «Danube circle», as well as the rapid development of the forms of early wheel-made pottery. The general profiling of vessels and design of the rim became more complicated, the rich linear-wavy ornament which covers practically all surface of the item became characteristic. This suggests the use of a quick hand wheel which has improved the symmetry of the vessels, as well as permitted to create the larger specimens. The evolution of the early wheel-made ceramic complex took place only by a variety of forms, however, technological indicators (dough composition, firing, density and thickness of vessel walls) indicate the actual invariability and sustainability of the manufacture tradition. The discontinuance of the functioning of the latest Raiky sites (Monastyrok and Kaniv settlements) can be attributed as the consequences of the first stages of consolidation of the Rus people in the Middle Dnieper dating to the late 9th — the turn of the 9th—10th centuries.